Electrochemical oxidation of methanol on Pt3Co bulk alloy - Gojković Snežana L. (Journal of the Serbian Chemical Society, 2003)
The electrochemical oxidation of methanol was investigated on a Pt3Co bulk alloy in acid solutions. Kinetic parameters such as transfer coefficient reaction orders with respect to methanol and H+ ions and energy of activation were determined. It was found that the rate of methanol oxidation is significantly diminished by rotation of the electrode. This effect was attributed to the diffusion of formaldehyde and formic acid from the electrode surface. Stirring of the electrolyte also influenced the kinetic parameters of the reaction. It was speculated that the predominant reaction pathway and rate determining step are different in the quiescent and in the stirred electrolyte. Cobalt did not show a promoting effect on the rate of methanol oxidation on the Pt3Co bulk alloy with respect to a pure Pt surface.